If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 9n = 8n Solving 7 + 9n = 8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-8n' to each side of the equation. 7 + 9n + -8n = 8n + -8n Combine like terms: 9n + -8n = 1n 7 + 1n = 8n + -8n Combine like terms: 8n + -8n = 0 7 + 1n = 0 Add '-7' to each side of the equation. 7 + -7 + 1n = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1n = 0 + -7 1n = 0 + -7 Combine like terms: 0 + -7 = -7 1n = -7 Divide each side by '1'. n = -7 Simplifying n = -7
| X^2-4x^4+8=0 | | 0.5+p(1-ln(p))=0 | | 12+9=9x+21 | | 12(x-2)=3(4x+5)-39 | | -45=-7(-3+6k)-2(5k+7) | | 4x^2+7=25 | | 4x^2-7=25 | | 2[(3+k)-7]=3[(3-k)-(-2)] | | 2(4x-3)-8=5+2x | | 2-(5x+3)=3(x+6)-2 | | 40-2x*e^2*x=0 | | P(x)=x^3+2x^2-8x | | -51=-4(8x+5)+7(x-8) | | -3x+2(2x+4)=-(4x+6)-6 | | 4X-1(3X+11)=-11 | | (a+b)*2= | | 0=6x^2-9x | | 4(2y-13)-9(y-3)+2(3y-10)=0 | | 2(-2y+1)=4y+18 | | n(n+1)+(n+2)=258 | | 0=x^2+9 | | 4(x-2)=2x-7+4x | | Y=2x^2+5x-1 | | -6(n+7)-5(6+3n)=-51 | | 8x+6m=26 | | 40-2x*e^2x=0 | | 0=2x^2+25x+5000 | | 4(x+9)-10x=-6(x+1)+10 | | 0=2x^2+25+5000 | | 12y-40=y-42 | | 5s-1=-11 | | -19=-3g+2 |